2020
DOI: 10.5194/esd-11-35-2020
|View full text |Cite
|
Sign up to set email alerts
|

Projecting Antarctica's contribution to future sea level rise from basal ice shelf melt using linear response functions of 16 ice sheet models (LARMIP-2)

Abstract: Abstract. The sea level contribution of the Antarctic ice sheet constitutes a large uncertainty in future sea level projections. Here we apply a linear response theory approach to 16 state-of-the-art ice sheet models to estimate the Antarctic ice sheet contribution from basal ice shelf melting within the 21st century. The purpose of this computation is to estimate the uncertainty of Antarctica's future contribution to global sea level rise that arises from large uncertainty in the oceanic forcing and the assoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
183
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

7
3

Authors

Journals

citations
Cited by 115 publications
(192 citation statements)
references
References 147 publications
(221 reference statements)
8
183
1
Order By: Relevance
“…Of the models that have carried out whole‐continent scenario‐based predictive simulations, many have employed simplifications to allow tractable experiments, such as excluding an evolving surface mass balance scheme (Ritz et al, ) or using simplified (time series) environmental forcings instead of spatially distributed climatologies (N. R. Golledge et al, ). These approximations aside, there is some agreement between scenario‐based ice sheet models that, under an unmitigated emissions scenario, Antarctica will contribute up to 40 cm to sea level by 2100 (N. R. Golledge et al, , ); Ritz et al, ; Schlegel et al, ), which is consistent with AR5 and previous modeling approaches that made projections using WAIS‐only models (Cornford et al, ) or that employed different methods for forecasting future mass loss, such as the “linear response function” approach (Levermann et al, , ).…”
Section: Near‐term Ice Sheet Contributions To Sea‐level Risesupporting
confidence: 67%
“…Of the models that have carried out whole‐continent scenario‐based predictive simulations, many have employed simplifications to allow tractable experiments, such as excluding an evolving surface mass balance scheme (Ritz et al, ) or using simplified (time series) environmental forcings instead of spatially distributed climatologies (N. R. Golledge et al, ). These approximations aside, there is some agreement between scenario‐based ice sheet models that, under an unmitigated emissions scenario, Antarctica will contribute up to 40 cm to sea level by 2100 (N. R. Golledge et al, , ); Ritz et al, ; Schlegel et al, ), which is consistent with AR5 and previous modeling approaches that made projections using WAIS‐only models (Cornford et al, ) or that employed different methods for forecasting future mass loss, such as the “linear response function” approach (Levermann et al, , ).…”
Section: Near‐term Ice Sheet Contributions To Sea‐level Risesupporting
confidence: 67%
“…Cornford et al (2015) found a 1.5 to 4.0 cm SLE in response to the A1B scenario from CMIP3, which is consistent with our findings, despite the A1B scenario being of a lower-magnitude forcing than RCP8.5. Furthermore, a 16-member ice sheet model inter- comparison study projecting the response to an RCP8.5 scenario by Levermann et al (2020) gave a 90 % likelihood upper-bound SLE contribution of approximately 9 cm relative to the year 2000, with a median of 2 cm. Whilst the uncertainty range in their investigation is derived from the differences between the ice sheet models, and thus their resolutions and model physics, the study does not account for uncertainty associated with individual model configuration, which would result in a greater uncertainty range in SLE projections.…”
Section: Discussionmentioning
confidence: 99%
“…Observations show that the Antarctic Ice Sheet is currently not in equilibrium and that its contribution to global sea level rise is increasing (Shepherd et al, 2018). Its future contribution is the largest uncertainty in sea level projections (Oppenheimer, 2020) with its evolution driven by snowfall increases (e.g., Ligtenberg et al, 2013;Frieler et al, 2015) that are counteracted by increased ocean forcing (e.g., Hellmer et al, 2012;Naughten et al, 2018) and potentially instabilities such as the marine ice sheet instability (Weertman, 1974;Schoof, 2007) and the marine ice cliff instability . In recent years, sea level projections of the Antarctic Ice Sheet were conducted with individual ice sheet models (e.g., and extended by comprehensive community efforts such as the Ice Published by Copernicus Publications on behalf of the European Geosciences Union.…”
Section: Introductionmentioning
confidence: 99%